Structured or unstructured educational robotics curriculum? A study of debugging in block-based programming - Socratous, Chrysanthos; Ioannou, Andri (My University, 2021)
The study aims to compare the effect of a structured versus an unstructured educational robotics (ER) curriculum on (a) the frequency and type of programming errors made by students in block-based programming, (b) their ability to debug a programme, and (c) their engagement in the learning process. The authors’ hypothesis is that, in programming contexts with young learners, an unstructured ER curriculum might be more beneficial in learning how to debug. This study follows a quasi-experimental design with two comparison groups (n = 35)—a structured ER curriculum group and an unstructured one. Within the quasi-experiment, both qualitative and quantitative data are collected. Findings reveal a list of errors commonly made by both groups. The unstructured ER curriculum group is associated with a significantly higher frequency of errors. The structured ER curriculum group demonstrates significantly greater efficiency in debugging. Yet, the students in the unstructured ER curriculum group outperform their peers in terms of engagement levels.
Keywords: Educational robotics; Block-based programming; Productive failure; Debugging; Primary education; Student engagement